How Urgent is Mobile Authentication in Special Need/Education? A Review Systematic of Cyber Security and Psychological Approach - Widyaningsih, Bernadeta Dhaniswara; Purnacandra, Amadeus Pondera (Journal of ICSAR, 2023)
The use of mobile apps due to the Covid-19 pandemic for the distance learning process, learning media, entertainment, and payment instruments creates an awareness of how urgently cyber security is needed in special education. Students, teachers, parents, and therapists, in special education who has interests and have the responsibility data, must be kept confidential or protected as the authenticity of their work, as well as the diversity of levels of disability, trying to study in a systematic review through scientific journal searches related to contemporary mobile authentication methods, authenticity. The review was conducted through several scientific search engines and mobile apps. The results show that authentication is a challenging study for mobile app (computing) developers but it is not easy to facilitate the unique, diverse needs of disability, and the privacy of personal data is still not following cyber security standards while the need for mobile apps in the health and education sectors is growing rapidly.